Surveillance of Antimalarial Drug-Resistance Genes in Imported Plasmodium falciparum Isolates From Nigeria in Henan, China, 2012–2019 - Zhao, Dongyang; Zhang, Hongwei; Ji, Penghui; Li, Suhua; Yang, Chengyun; Liu, Ying; Qian, Dan; Deng, Yan; Wang, Hao; Lu, Deling; Zhou, Ruimin; Zhao, Yuling (Frontiers in Cellular and Infection Microbiology, 2021)
Malaria remains a major public health issue in Nigeria, and Nigeria is one of the main sources of imported malaria in China. Antimalarial drug resistance is a significant obstacle to the control and prevention of malaria globally. The molecular markers associated with antimalarial drug resistance can provide early warnings about the emergence of resistance. The prevalence of antimalarial drug resistant genes and mutants, including PfK13, Pfcrt, Pfmdr1, Pfdhfr, and Pfdhps, was evaluated among the imported Plasmodium falciparum isolates from Nigeria in Henan, China, from 2012 to 2019. Among the 167 imported P. falciparum isolates, the wild-type frequency of PfK13, Pfcrt, Pfmdr1, Pfdhfr, and Pfdhps was 98.7, 63.9, 34.8, 3.1, and 3.1%, respectively. The mutation of PfK13 was rare, with just two nonsynonymous (S693F and Q613H) and two synonymous mutations (C469C and G496G) identified from four isolates. The prevalence of Pfcrt mutation at codon 74–76 decreased year-by-year, while the prevalence of pfmdr1 86Y also decreased significantly with time. The prevalence of Pfdhfr and Pfdhps mutants was high. Combined mutations of Pfdhfr and Pfdhps had a high prevalence of the quadruple mutant I51R59N108-G437 (39.0%), followed by the octal mutant I51R59N108-V431A436G437G581S613 (17.0%). These molecular findings update the known data on antimalarial drug-resistance genes and provide supplemental information for Nigeria.